Art Threats and First Amendment Disruption - Kerr, Andrew Jensen (2015)
The novel problem of art threats, typified by threatening rap lyrics, has destabilized our First Amendment regime. We have traditionally relied on industry gatekeepers like music labels or museum curators to determine what counts as art. However, with the advent of the Internet, amateur artists can share their aesthetic output with a public audience, bypassing the threshold quality control work of the Art World. This has forced courts to acknowledge foundational questions about what kind of art is covered by the First Amendment. In brief, it covers “good” art. In this paper I offer a synthetic conception of the First Amendment that contextualizes this aesthetic gatekeeper problem within a freedom of speech doctrine that has been forced to distinguish art from threat. I echo the claims of law and rap scholars that the amateur attempt at rap should be interpreted within a permissive standard for political speech, but I remind this scholarly network that our category of art speech still connotes a threshold level of quality. Young artists need help with self-editing; they do not need to be punished. But this does not mean the amateur attempt at art should be reified as good art within our constitutional law doctrine. I thus consider some pragmatic solutions for how either civil society or the state can mirror the essential quality control work done by prior Art World actors. My thinking is informed by a noble understanding of rap as well as the cultural assumptions that explain the boundaries of the First Amendment